Continuous buttermaking : a process capability study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology in Industrial Management at Massey University - Stockwell, Dean Thomas John (Massey University, 1972)
Continuous buttermaking has become an important process in the New Zealand Dairy Industry. From the first experimental trials in 1964 conducted by staff of the New Zealand Dairy Research Institute, continuous manufacture of butter by the Fritz process has now reached a commercial production of over 80,000 tons. Process control of the buttermaking process plays an important part in determining the economic return on the product. At this stage adequate information is available on the general operating principles of Continuous churns. However, in the absence of change in the operating conditions the product continues to show compositional variation. There is little information available to determine the causes of such variation. The work undertaken during this project was primarily aimed at investigation of this variation. It was conducted as a process capability study. It is clear that Continuous Buttermaking will continue to be an important process in the New Zealand Dairy Industry for some time, and it is essential that further information regarding the proceas is made available in order to facilitate improved process control.
Keywords: Butter -- Manufacture